MAX WEBER’S IDEAL BUREAUCRACY AND THE REALITY OF LAW ENFORCEMENT IN INDONESIAN VILLAGES - Ahmad Gautsul Anam; Muhammad Surur (GEMOVE: Journal of Gender, Movement, and Empowerment, 2026)
This article examines the gap between Max Weber's ideal bureaucratic model and the reality of village-level law enforcement in Indonesia. Weber posited that a rational-legal bureaucratic system, characterized by clear rules, specialized competence, and impartial administration, would serve as the foundation of modern governance. However, the village governance structure in Indonesia, particularly following the enactment of Law Number 6 of 2014 concerning Villages, reveals significant deviations from this ideal. This study employs a normative legal research method with a comparative and analytical approach, analyzing the legal framework governing village law enforcement and situating it within Weber's theoretical lens. The findings indicate that the village legal apparatus suffers from structural weaknesses including overlapping authority, limited human resources, and the persistence of traditional and charismatic authority structures that compete with rational-legal norms. Furthermore, weak institutional capacity at the village level leads to inconsistent and often ineffective law enforcement outcomes. This article concludes that strengthening village-level law enforcement requires not only legislative reform but also a sustained effort to build rational-legal institutional capacity in accordance with Weberian principles of bureaucratic efficiency and impartiality.